Degree of Alignment Between Japanese Patients and Physicians on Alopecia Areata Disease Severity and Treatment Satisfaction: A Real-World Survey - Kouki Nakamura; Kazumasa Kamei; Jenny Austin; Simran Marwaha; James Piercy; Peter Anderson; Masayo Sakaki-Yumoto; Manabu Ohyama (Adis, Springer Healthcare, 2023)
Abstract Introduction Alopecia areata (AA) is characterized by non-scarring scalp and/or body hair loss and can negatively impact patient mental health. Data are limited on the alignment of patient and physician perceptions of AA severity with each other and with Japanese Dermatological Association (JDA) guideline criteria, and of patient-physician alignment on treatment satisfaction. Therefore, we performed analyses to compare JDA severity groupings with patient-physician alignment on disease severity and to explore treatment satisfaction in AA in Japan. Methods Data were drawn from the Adelphi AA Disease Specific Programme (DSP)™, a real-world survey of physicians and patients with AA in Japan conducted January-March 2021. Patients and physicians reported patient AA severity as mild, moderate or severe based on their subjective judgement. Patients were then categorized into five hair loss severity groups according to JDA criteria (S1-5), and patient-physician pairs were matched to assess alignment on severity and treatment satisfaction. Results Subjective patient- and physician-reported disease severity generally followed JDA severity groupings. The percentage of patient-physician alignment on severity recognition was 76.3% in the overall population. In misaligned pairs, 20.2%, 14.5%, 7.3%, 25.0% and 0.0% of physicians rated disease as more severe than patients in S1, S2, S3, S4 and S5, respectively. Regarding treatment satisfaction, patient-physician alignment was 57.6% in the overall population. In S5, 46.2% of physicians reported being less satisfied than patients. Both physicians and patients cited lack of efficacy as the main reason for dissatisfaction. Of 221 patients, 39.8% and 29.9% were categorized as borderline-abnormal cases for anxiety and depression, respectively. Conclusions This study highlights previously unreported patient-physician misalignment on disease severity, level of treatment dissatisfaction and unmet needs due to the lack of effective treatment. Further study on how improvement of the misalignment between physicians and patients could increase both patient and physician satisfaction with treatment and improve the quality of life for patients with AA.